2010
DOI: 10.1007/s00167-010-1216-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased medial tibial slope in teenage pediatric population with open physes and anterior cruciate ligament injuries

Abstract: PurposeVariations in bony morphology have been associated with anterior cruciate ligament (ACL) injury risk. The primary aim of this study was to compare the tibial slope in the teenage pediatric population with open physes, with and without ACL injury. The secondary aims were to compare the notch width index (NWI) and determine the influence of gender and age on tibial slope and NWI.MethodsThirty-nine teenage pediatric subjects were included in this study, 16 with and 23 without ACL injury. Medial tibial slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
122
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 32 publications
1
122
3
Order By: Relevance
“…3 Of the 6 studies that compared LTPS in ACL-injured and uninjured groups as a whole, 1 radiographic study and 1 MRI-based study found no significant difference between injured and uninjured groups. 18,41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Of the 6 studies that compared LTPS in ACL-injured and uninjured groups as a whole, 1 radiographic study and 1 MRI-based study found no significant difference between injured and uninjured groups. 18,41 …”
Section: Resultsmentioning
confidence: 99%
“…3,36 For ACL-injured patients, the medial slope ranged from 1.8° ± 3.5° anterior to 12.1° ± 3.3° posterior. 3,41 Figure 4 shows the absolute measurements for MTPS by study. The unweighted mean effect size for the 13 studies was .388, indicating a more posterior MTPS in ACL-injured populations than controls.…”
Section: Resultsmentioning
confidence: 99%
“…slope was associated with ACL tear [5,13,40,43,44,46]; on the contrary, others rejected this correlation [4,8,15,17,18,39,42]. Moreover, there exist two metaanalyses came to totally opposite conclusions [48,49].…”
mentioning
confidence: 93%
“…Femoral notch characteristics and tibial plateau slope and/or depth have been proposed as morphologic risk factors possible to identify from standard X-ray evaluation (Vyas et al 2011;Smith et al 2012b;Wordeman et al 2012). Females are more likely than males to have a narrow A-shaped intercondylar notch which has been associated to gender-specific risk factor (Sutton and Bullock 2013).…”
Section: Radiographic Assessment Of Bone Morphology Risk Factorsmentioning
confidence: 97%
“…Females are more likely than males to have a narrow A-shaped intercondylar notch which has been associated to gender-specific risk factor (Sutton and Bullock 2013). However, notch width index has not been considered a feasible method (Vyas et al 2011). …”
Section: Radiographic Assessment Of Bone Morphology Risk Factorsmentioning
confidence: 99%